2016
DOI: 10.1007/s11064-016-1969-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Histone Deacetylase Inhibitors Affects Gene Expression of Autism-Related Molecules and Delays Neuronal Maturation

Abstract: Valproic acid (VPA) is a multi-target drug and an inhibitor of histone deacetylase (HDAC). We have previously demonstrated that prenatal exposure to VPA at embryonic day 12.5 (E12.5), but not at E14.5, causes autism-like behavioral abnormalities in male mouse offspring. We have also found that prenatal VPA exposure causes transient histone hyperacetylation in the embryonic brain, followed by decreased neuronal cell numbers in the prefrontal and somatosensory cortices after birth. In the present study, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…Although VPA is a commonly used antiepileptic drug worldwide, its toxicity and teratogenicity is a relevant problem especially in the treatment of women at childbearing age [35]. Prenatal VPA exposure of neuronal cultures from the cerebral cortices of prenatal mice embryos was shown to decrease the total number, total length, and complexity of neuronal dendrites [36]. Similarly, results obtained by Semmler et al [37] indicated that intrauterine VPA exposure caused dose-dependent neuronal cell number alterations in the hippocampal areas CA1/2 and the CA3 region and in folic acid metabolism in a rat model of valproate teratogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although VPA is a commonly used antiepileptic drug worldwide, its toxicity and teratogenicity is a relevant problem especially in the treatment of women at childbearing age [35]. Prenatal VPA exposure of neuronal cultures from the cerebral cortices of prenatal mice embryos was shown to decrease the total number, total length, and complexity of neuronal dendrites [36]. Similarly, results obtained by Semmler et al [37] indicated that intrauterine VPA exposure caused dose-dependent neuronal cell number alterations in the hippocampal areas CA1/2 and the CA3 region and in folic acid metabolism in a rat model of valproate teratogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Valproate, a well-known HDAC inhibitor drug, induces important delays in neuronal maturation [34], already described in ASD [35]. Moreover, VPA prenatal exposure alters the postnatal histone 3 (H3) acetylation levels in the cerebellum [36], stimulates glial cell proliferation in the developing rat brain [37], and also induces changes in acetylation levels in the astrocytes of the hippocampus and cortex in cell culture more than other antidepressants and mood stabilizers do [38].…”
Section: Histone-deacetylases Inhibitors and Neuroimmune Alterationsmentioning
confidence: 99%
“…However, VPA exposure alters expression of a wide range of genes in addition to Bdnf , including some that could dysregulate brain development and function if overexpressed in the fetal brain [68]. The results reported here show that, following in utero VPA exposure, there is more Ex1- and Ex4- Bdnf mRNA in female than in male fetal brains.…”
Section: Discussionmentioning
confidence: 78%